Science, fiction, and Santa Claus: Hollywood creator and consultant perceptions of fictional science in film and television - Davis, Jessica L.; Savoie, Gianna; Longnecker, Nancy (Frontiers in Communication, 2023)
From the high-stakes operating room of a Seattle hospital, to the shattered remains of a planet in a galaxy far, far away, Hollywood is often critiqued for its representations of scientific knowledge, methods, and/or technology. Existing research into Hollywood representations of science focuses primarily on those that do not align with expert consensus, and on how audiences engage with these representations — such as how misinformation in fictional narratives influences us. This paper, instead, approaches the matter of fictional science in fictional narratives (FiSci) from the perspectives of the individuals creating Hollywood content. We use the label of “FiSci” for any representation of science within a narrative which does not align with humanity’s current knowledge or technological capability. Semi-structured interviews were conducted in late 2020 with a purposefully-selected sample of both Hollywood creators (writers, directors, and producers; n = 28) and science experts who have served as consultants (n = 18) across a range of film and television projects. Thematic analysis was used to explore how these creators and consultants perceive FiSci and its role within Hollywood narratives. Three themes were constructed from the interview data. Participants primarily spoke of FiSci as: (1) a storytelling tool, perceived either positively or negatively, depending upon how that tool is wielded; (2) a way to play within a constructed storyworld which does not resemble our own; and (3) a source of unrealistic “B.S.” which threatens to break audience suspension of disbelief and can signify a lack of effort in the creative process. This paper contributes to science communication research by providing access to minds behind the representations of science in Hollywood film and television. As such, it can be used to aid the creator-consultant relationship and the implementation of FiSci to the benefit of both groups. It may also inform creators who have yet to work with a consultant, experts looking to become consultants, audiences critiquing FiSci in the content they watch, and experts and science communicators who express concerns about the use of FiSci and the responsibilities of Hollywood.